A constructionist approach to Arabic active participles - Ayman Yasin; Osama Abdelghafer (Cogent Arts & Humanities)
This paper aims at analyzing the active participle in Modern Literary Arabic. In this type of nominalization, the active participle is ambiguous between a nominal and a verbal reading. We first show how this construction is similar to nominal structures; then we explain how it exhibits verb-like properties; we further argue that, in spite of the verbal properties, this construction is best analyzed as an instance of non-verbal predication. Last, using Distributed Morphology, we show how the active participle projects into a root clause.